2016
DOI: 10.1103/physrevb.93.085202
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle band gap of organic-inorganic hybrid perovskites: Crystal structure, spin-orbit coupling, and self-energy effects

Abstract: The quasiparticle band gap is one of the most important materials properties for photovoltaic applications. Often the band gap of a photovoltaic material is determined (and can be controlled) by various factors, complicating predictive materials optimization. An in-depth understanding of how these factors affect the size of the gap will provide valuable guidance for new materials discovery. Here we report a comprehensive investigation on the band gap formation mechanism in organicinorganic hybrid perovskites b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 61 publications
8
63
0
Order By: Relevance
“…Photoluminescence spectra results show that there is a change in the energy of the maximum photoluminescence intensity at the 150 K transition 61 , in agreement with the observation made here that the key change in whole body molecular dynamics is at this temperature. This suggests that it is the whole body rotations of the MA cation and their interactions with the surrounding inorganic framework 12 that is key to understanding the photovoltaic properties. However, it is important to note that the change in pho-toluminescence observed at 150 K is not large.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoluminescence spectra results show that there is a change in the energy of the maximum photoluminescence intensity at the 150 K transition 61 , in agreement with the observation made here that the key change in whole body molecular dynamics is at this temperature. This suggests that it is the whole body rotations of the MA cation and their interactions with the surrounding inorganic framework 12 that is key to understanding the photovoltaic properties. However, it is important to note that the change in pho-toluminescence observed at 150 K is not large.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogen bonding has been identified as strongly linked with the octahedral tilts of the system, and the phase transitions within the system, with the hydrogen bonding stronger in the low-T phase where the molecular motion is lower 17,18,22,62 . Due to the fact that the structure is so heavily dependent on the cation dynamics, this then influences the band gap of the system, with the states near the top of the valence band stabilized by the octahedral tilting in the low temperature phase with fewer cation dynamics 12,17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for realistic structures in working devices, which often are compounds with mixtures of more than one organic cation, metal cation or halide anion with sophisticated surfaces and interfaces [1][2][3][4][5][6][7] . The challenges to fundamental understanding of the electronic structure of AMX 3 perovskites stem from their rich chemical and physical properties and the interplay of these properties 6,7 Several research groups [8][9][10][11][12][13][14][15][16] have successfully applied the GW method to predicting electronic structures of AMX 3 perovskites. Even et al 8 have identified the importance of a giant spin-orbit coupling (SOC) effect (about 1.0 eV) in the lead iodide perovskites, acting mainly on the conduction band (mainly consisting of Pb states).…”
mentioning
confidence: 99%
“…The same group of researchers also looked at the substitution of halide ions in CH 3 NH 3 PbX 3 11 and nicely reproduced experimental findings in optical behavior, such as an increase of the band gap when moving from I to Cl. A few other theoretical studies at GW level include the investigation of polar phonons 12 , crystal structure effects and phase transitions 13,14 , exciton binding energies 15 , and band gap trends 16 in AMX 3 . The above mentioned GW studies have been very important in understanding the chemistry and physics of these materials and providing materials design inspirations.…”
mentioning
confidence: 99%